Ceramic deposition and midden formation in Kalinga, Philippines - Beck, Margaret E. (ProQuest Information and Learning Company, 2003)
This ethnoarchaeological study addresses refuse disposal and site formation processes in a village setting, focusing on one artifact class (ceramics) and one type of refuse accumulation (middens). Archaeologists have long relied on middens for large artifact samples. Midden ceramics in particular can contribute to studies of household and community composition, activities, status differences, and food-preparation methods, but interpretations often require linking discarded ceramics to their source, if only in a general sense, and assessing the representativeness of the ceramic sample. This case study provides a model for determining midden catchments, illustrates the variables affecting ceramic deposition, and compares midden ceramics to systemic ceramic assemblages. The deposits themselves are also described in detail, linking observed midden formation processes with the resulting physical and chemical properties. Fieldwork was conducted in February-July 2001 in Dalupa, Kalinga Province, the Philippines, as part of the Kalinga Ethnoarchaeological Project. Residents of Dalupa are subsistence rice farmers, and traditional ceramic production continues despite the availability of metal and plastic alternatives. The 71 households in the community participated in household vessel inventories and weekly interviews to track ceramic vessel breakage and general discard patterns. Thirty active middens were identified in Dalupa, occupying roughly nine percent of the residential area. Twenty-eight of these middens were characterized using some or all of the following methods: surface maps, surface transects for artifact recording and collection, systematic cores for depth, pH measurements, excavated test units, and chemical analysis of soil samples. Observations of midden activity and soil profiles in and around Dalupa provide information on cultural and natural disturbance processes.--Abstract.